2021
DOI: 10.1088/1741-2552/abf290
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical interfaces with cortical spheroids in three-dimensions

Abstract: Three-dimensional (3D) neuronal spheroid culture serves as a powerful model system for the investigation of neurological disorders and drug discovery. The success of such a model system requires techniques that enable high-resolution functional readout across the entire spheroid.Conventional microelectrode arrays and implantable neural probes cannot monitor the electrophysiology activity across the entire native 3D geometry of the cellular construct. Here, we demonstrate a 3D self-rolled biosensor array (3D-SR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…We further confirm that the signal recorded is from the brain organoids by examining the response to 20 μM glutamate neurotransmitter added to the culture medium served as a positive control for the spontaneous recording (23,37). The spike signal-to-noise ratio (SNR) before and after the glutamate application showed statistically significant amplification (median increased by 57.6%) on the amplitude of firing spikes (Fig.…”
Section: Feasibility Of Spontaneous Activity and Glutamate-induced El...supporting
confidence: 60%
See 3 more Smart Citations
“…We further confirm that the signal recorded is from the brain organoids by examining the response to 20 μM glutamate neurotransmitter added to the culture medium served as a positive control for the spontaneous recording (23,37). The spike signal-to-noise ratio (SNR) before and after the glutamate application showed statistically significant amplification (median increased by 57.6%) on the amplitude of firing spikes (Fig.…”
Section: Feasibility Of Spontaneous Activity and Glutamate-induced El...supporting
confidence: 60%
“…Kalmykov et al . have developed a cylindrical sensor array for cardiac and cortical organoids ( 21, 23 ). This methodology requires manual unrolling of the cylinder with a micromanipulator to enclose the organoids which can limit throughput and also has a limited cylindrical shape.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, work by Kim et al (2011) and Zhang et al (2013) (Kim et al, 2011;Zhang et al, 2013) have demonstrated that serpentine electrode interconnects incorporated within ultra-thin substrate materials can form extremely stretchable interfaces that can conform to different types of biological tissue, with modulus of elasticity that can range between 100 MPa to 300 kPa. Additionally, devices embedded in SU-8 have also achieved electrophysiological interfaces using complex 3D geometries (e.g, self-rolled spheroids) (Kalmykov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%